2021
DOI: 10.1590/1806-9061-2019-1176
|View full text |Cite
|
Sign up to set email alerts
|

Response of Broiler Chicks to Dietary L-Leucine Supplementation in the Starter Period

Abstract: This experiment was conducted to investigate the effects of leucine (Leu) supplementation on performance and carcass traits of broilers along with the re-evaluation of standardized ileal digestible (SID) Leu requirement of broiler chicks on days 0-14. Birds were fed seven experimental diets with SID Leu levels of 16.3 (basal), 17.3, 18.3, 19.3, 20.3, 21.3, and 22.3 g/kg. Some 280 male broiler chicks were randomly assigned to the seven dietary treatments in a completely randomized design with five replicates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 34 publications
5
3
2
Order By: Relevance
“…This indicates that the plasma and intracellular levels of leucine were below the minimum needed for protein accretion. 14,16 The decreased FI in the LPD, LLPD and HLPD groups during the starter phase indicates that FI was negatively affected by the quantity and quality of dietary protein, as aligned with a previous finding. 4 Disproportionate levels of leucine in broiler diets cause an imbalance in the ratio among BCAAs 10,11 and probably antagonistic effects on the valine.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This indicates that the plasma and intracellular levels of leucine were below the minimum needed for protein accretion. 14,16 The decreased FI in the LPD, LLPD and HLPD groups during the starter phase indicates that FI was negatively affected by the quantity and quality of dietary protein, as aligned with a previous finding. 4 Disproportionate levels of leucine in broiler diets cause an imbalance in the ratio among BCAAs 10,11 and probably antagonistic effects on the valine.…”
Section: Discussionsupporting
confidence: 88%
“…5,9,10 Also, during the starter phase, the decrease in the FI of the LLPD broilers could have induced a deficiency of isoleucine and valine as well, which is associated with growth depression. 8 The results concerning the impacts of the LLPD treatment on the carcass and non-carcass components agreed with the findings of Kratei and Shahir, 14 who reported that dietary leucine supplementation improved carcass and breast yields. However, our results on the relative abdominal fat weight and the fat contents of the studied meats did not confirm the hypothesis that leucine plays a regulatory role in fat reduction.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations